Artificial recharge endeavours in India: a review - Saha, D.; Sikka, Alok; Goklani, Rahul (Elsevier, 2022)
In India, artificial recharge (AR) of aquifers is considered a primary supply-side measure to combat the widespread over-exploitation of groundwater. As a major collateral benefit of rainwater harvesting (RWH) is aquifer rejuvenation, both rainwater harvesting and AR are planned and executed as a set of coherent interventions. The Central and state governments have brought in several schemes involving AR and RWH. Moreover, a number of researches are being conducted on how to select the sites for structure construction, the types of structure and their designs depending upon the local hydrogeology, groundwater flow regime, terrain condition and demand of water, and how they impact on resource rejuvenation and improvement in water quality. Various researches are also available on how such endeavors are translating into socio-economic benefits. The paper reviews the researches that have been done in India on these issues and related government policies and schemes under execution. The critical issues like source water availability for recharge, upstream-downstream conflicts, and the rising awareness of different demand-side interventions for sustainable management of groundwater resources have also been discussed.